EVALUATION OF ANTIOXIDANT AND ANTIULCER ACTIVITY OF METHANOLIC EXTRACT OF GARDENIA GUMMIFERA L. IN RATS - Sabbani, Pradeep Kumar; Kumar Chityala, Pavan; Nl, Gowrishankar; Kumar, Naveen; K, Shilpa (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: The aim was to assess the effect of anti ulcer and anti oxidant activity of methanolic extract of Gardenia Gummifera (MEGG) whole plant in ulcer induced rats and in-vitro anti oxidants method respectively. Methods: In the present study, the efficacy of an MEGG was evaluated against aspirin-induced ulcers in rats. G. gummifera at doses of 150 mg/kg and 300 mg/kg was administered orally once daily for 6 days. Results: Results showed that extract treatments prevented ulcer area and gastric secretion in a dose-dependent manner. Administration of 2000 mg/kg extract did not show any toxicity in albino mice. In preliminary phytochemical studies identified the presence of flavonoids in the MEGG. Conclusion: According to the results, it was concluded that the whole plant of G. gummifera has significant antiulcer activity due to the presence of potent antioxidants like flavonoids. Keywords: Aspirin, Antiulcer, Hydrogen peroxide, Gardenia gummifera.